THE SACRAMENTO DISTRIBUTION - SACRAMENTO, Vinicius Pereira do; SACRAMENTO, Katia Pires Nascimento do; Alixandre Ávila RODRIGUES, Francisco (Brazilian Journal of Biometrics, 2021)
In this article, we present the Sacramento distribution of two parameters. This model competes e ectively with the distributions used in the fault data analysis because it has a non-monotonous hazard function that can shape many forms of hazard. Some mathematical properties of the new distribution are also presented, including hazard function, survival, general formula for moments. The maximum likelihood method is used to estimate the model parameters. We obtain the expected information matrix and discuss inference methods. Finally, two real data sets are analyzed and comparisons are made between the new distribution with the Burr XII, Burr III and Beta Prime distributions to show the exibility and potential of the new distribution.